Analysis of Meshing Mechanical Characteristics of Crown Gears Coupling with Transition Gear Sleeves - Wang Xiaoyi; Zhang Zhiwei; Zhang Guotao; Xia Qinghua; Yang Xiaohong; Li Tianchao; Zhu Changjiang (Jixie chuandong)
The meshing mechanical characteristics of crown gear pairs have an important impact on the bearing capacity and transmission performance of crown gear coupling. Based on the conventional crown gear pair structure, a late-model of crown gear pairs with transition gear sleeves is proposed, the meshing mechanical characteristics of crown gear pair are analyzed, and the influence of different inclination angles on the meshing mechanical characteristics of crown gear pairs is discussed. The results show that the maximum equivalent stress and strain of the conventional crown gear pair occurs on the internal gear shaft sleeve, and the maximum equivalent stress and strain of the new crown gear pair occurs on the transition gear sleeve; compared with the conventional gear pair system, the maximum equivalent stress in the new gear pair system is reduced by 32.12%, and the maximum equivalent strain is reduced by 21.4%. The stress concentration of the external gear shaft sleeve of the conventional gear pair occurs at the tooth root, and the stress concentration of the external gear shaft sleeve of the new gear pair occurs at the middle bulge position； compared with the conventional gear pair, the maximum equivalent stress of the external gear sleeve in the new gear pair is reduced by 15.75%. With the increase of the inclination angle between shafts, the maximum equivalent stress and strain in the conventional gear pair increase, while the equivalent stress and strain of the external gear sleeve in the new gear pair is partially transferred to the transition gear sleeve. Therefore, the external gear shaft sleeve in the new structure can still maintain a lower equivalent stress under a larger inclination angle, which can effectively protect the expensive external gear shaft sleeve.